Recent advances in pericardium extracellular matrix for tissue regeneration, along with a short insight into artificial intelligence - Shariat Rad, Parand; Khazaei, Mozafar; Ghanbari, Elham; Rashidi, Mehdi; Rezakhani, Leila (Frontiers in Medical Technology, 2025)
Medical science is striving to find new solutions to treat various diseases. Tissue engineering with a great potential to develop tissues and even organs from synthetic and biological materials, open a new gate toward absolute treatments. Although in tissue engineering as a subtype of regenerative medicine, decellularized tissues are new, promising way to fill the previous methods gaps. Outside of the biological aspects, artificial intelligence (AI) and machine learning (ML) are applied to tissue engineering. Decellularization is a very important area where AI supports protocols and ensures the process is repeated identically each time. It also greatly assists in monitoring the extracellular matrix (ECM) to ensure it remains intact. Nonetheless, the use of AI in tissue engineering is not fully discussed in scientific articles. Although based on the tissue used for decellularization these features could vary, to optimize decellularization we need new method to reach high accuracy. In these current days, Pericardium, a double-layered membrane around the heart of mammalians, as a natural ECM has been utilized in cardiac surgery for many years. However, the use of decellularized pericardium as a scaffold for tissue engineering has gained significant attention in recent times, due to its retention strength, flexibility, supports for cell growth and differentiation, etc. That altogether put it among the top choices for tissue engineering and regenerative medicine. In this review we aim to cover the different decellularization methods, application of decellularized pericardium, commercial products that are available and challenges and future direction of this potent therapy.